Synthesis and characterization of Ferric Sorbate and Aluminum Sorbate as antifouling pigments for marine paints - Perez, Miriam Cristina (2014)
Biofouling is a natural process that involves the settlement and growth of organisms on natural or man-made structures and leads to material deterioration, generating severe technical and economic problems. The use of paints has been a practical method to control marine biofouling. However, some biocides currently employed have been banned because of their toxicity. There is a growing need for environmentally safe antifouling systems. The current study describes the synthesis and characterization of two new pigments, ferric sorbate and aluminum sorbate, as potential antifoulants. Laboratory assays with fouling organisms and field trials with antifouling paints were conducted. The antifouling activity of sorbate-pigment-based paints was successful and could be attributed to the combined action of a sorbate anion and low pH values generated by hydrolysis at the paint/seawater interface. After 9 months of exposure in the sea, paints containing synthetic sorbate salts had much lower fouling settlement compared to controls, indicating that these pigments are promising candidates for biofouling control.